Effect of fiber orientation on tribological behaviour of Typha angustifolia natural fiber reinforced composites. (2022) - Mohankumar, D.; Rajeshkumar, L.; Muthukumaran, N.; Ramesh, M.; Aravinth, P.; Anith, R.; Balaji, S.V.
Abstract: Natural fiber reinforced composites are replacing the synthetic fibers rapidly during the recent days owing to their numerous advantages. Current work focusses on evaluating the hardness and tribological behaviour of Typha angustifolia fiber reinforced (TAFR) epoxy composites. Composites were fabricated with three different volume fraction of fibers such as 10%, 15% and 20% using compression moulding method. Fiber orientations were kept as unidirectional (UD) and bidirectional (BD) and composites were manufactured separately with the aforesaid fiber content. Hardness of the composites were evaluated using Shore-D hardness tester and the wear and coefficient of friction of the composites were assessed using pin-on-disc tester as per ASTM standards. Tribological behaviour of TAFR composites was measured under different loads such as 10, 20, 30, 40 and 50 N for which the specific wear rate (SWR) and coefficient of friction (CoF) were evaluated. Effect of fiber orientation on tribological behaviour of the TAFR composites were assessed. From the hardness test results, it could be seen that BD composites exhibited higher hardness when compared with UD composites and 20% composites outperformed its counterparts. Similarly, SWR decreased and CoF increased with increase in load on the TAFR composites while the rate of increase was relatively lesser for 20% TAFR composites. It could be seen from the experiments that 20% composites exhibited better behaviour comparatively.